Preferensi Investor di Sekitar Cum-Dividend Date Sebelum dan Saat Masa Pandemi Covid-19 - Millawati, Ni Putu Shanti; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 34 No 2 (2024)DO - 10.24843/EJA.2024.v34.i02.p01, 2024)
This study aims to determine investor preferences around cum-dividend date before and during the Covid-19 pandemic. The population in this study were companies registered in IDX30 before the pandemic with 120 companies and 90 companies during the pandemic. The sample of this study was determined by purposive sampling and obtained 70 companies before the pandemic as well as 61 companies during the pandemic. The data analysis technique used is paired sample t-test and independent sample t-test. The results of this study showed that there was no significant difference in trading volume activity and bid-ask spread around the cum-dividend date before and during the Covid-19 pandemic. However, there was a significant difference in trading volume activity before and after cum-dividend date before the pandemic. The results of this study also showed that investors preferences for dividends are more likely to be attracted during the Covid-19 pandemic. Keywords: Investor Preferences; Cum-Dividend; Covid-19